2021
DOI: 10.1108/jedt-01-2021-0049
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying cost misperception as a challenge to green building adoption in Nigeria

Abstract: Purpose The pertinent information about green buildings (GB) is laden with cost misperceptions (CM) that are paraded into adoption decisions without factual clarifications. The unsupported beliefs are fundamental to the disparaging low adoption of related technologies globally. The purpose of this paper is to explore the causes of CMs among construction stakeholders and why is it difficult to discredit this information? Design/methodology/approach The research adopted two-tier approaches involving a Delphi s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Collins (2010) acknowledged that Likert scales are effective to elicit participants’ opinions on various statements. Previous studies on sustainability have also embraced the use of questionnaire surveys (Oluleye et al , 2020; Afum et al , 2021; Ekung et al , 2021). To validate the research instrument, a pilot survey including five professionals and three lecturers in academia was conducted to ensure the unsustainable practices, barriers and strategies identified from the literature apply to the Nigerian context.…”
Section: Methodsmentioning
confidence: 99%
“…Collins (2010) acknowledged that Likert scales are effective to elicit participants’ opinions on various statements. Previous studies on sustainability have also embraced the use of questionnaire surveys (Oluleye et al , 2020; Afum et al , 2021; Ekung et al , 2021). To validate the research instrument, a pilot survey including five professionals and three lecturers in academia was conducted to ensure the unsustainable practices, barriers and strategies identified from the literature apply to the Nigerian context.…”
Section: Methodsmentioning
confidence: 99%
“…(2022) brought forward five unsustainable practices in Nigeria to include; negative externalities, excess energy, unsustainable technologies, non-management of health and safety of workers and material waste. In their work, Ekung et al. (2022) noted that low knowledge of green building practices, non-familiarity with performance metrics, inadequate evidence and poor-risk perceptions distorts stakeholders' adoption to green building in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By 2022,Omopariola et al (2022) brought forward five unsustainable practices in Nigeria to include; negative externalities, excess energy, unsustainable technologies, non-management of health and safety of workers material waste. In their work,Ekung et al (2022) noted that low knowledge of green building practices, non-familiarity with performance metrics, inadequate evidence and poorrisk perceptions distorts stakeholders' adoption to green building in Nigeria. In the same year, Omopariola et al (2022) further revealed six new barriers of SC to include, absence of historical data and exemplary projects on which construction professionals can build and learn from; lack of professional to handle task; poverty and low urban investment; lack of urban and construction policy; lack of awareness; and lack of technical knowhow.…”
mentioning
confidence: 99%
“…The two major design characteristics that are critical to all Delphi panels, irrespective of topic or approach are anonymity and feedback; and the lack of these two characteristics will flaw any presumed Delphi design (Yousuf, 2007;Ameyaw, 2015;Avella, 2016). Ekung et al (2021) opined that no clear guidelines are suggesting the numbers to be included in studies applying the Delphi survey because the sample is purposively selected and it depends on the problem being investigated. Agumba and Musonda (2013) opined that a Delphi study can be conducted with as few as eight panel members if the background of the panellists was homogenous.…”
Section: Expert Panellists and Requirementsmentioning
confidence: 99%